THE INFLUENCE OF LEARNING APPROACH AND MOTIVATION ON MATHEMATICS LEARNING RESULTS OF CLASS V STUDENT AT SD IN BULUKUMBA DISTRICT - Nur Hidayah Basri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The research is experiment which aims to discaver: (i) the influence of approach, learning, and interaction collaboratively on learning result, (ii) the difference of mathematics learning results of the student who were taught by employing Realistic Mathematic Education (RME) approach and problem posing approach, (iii) the difference of mathematics learning results of students who have very high and high motivation, (iv) the interaction influence of learning approach with motivation on mathematics learning result, (v) the difference of mathematics learning results of the students who were taught by employing RME approach with very high and high motivation, (vi) the difference of mathmatics learning results of the studentswho were taught by employing problem posing approach with very high and high motivation, (vii) the difference of mathematics learning results of the student who have very high motivation taught by employing RME approach and problem posing approach, and (viii) the difference of mathematics learning results of the student who have high motivation taught by employing RME approach and problem posing approach of class V student at SD in Bulukumba District. The populations of the research were all class V students at SD in Bulukumba District of Academic Year 2015/2016. From the populations, two classes were chosen by using cluster random sampling method as the sample. The instruments of the research after validated covered learning implementation observation, motivation questionnaire, test, and observation sheets. Then, it was analyzed by using descriptive analysis and ANAVA. The results of the research reveal that (i) there is inflence of approach, learning, and interaction collaboratively on the students’ learning results, (ii) there is no difference of mathematics learning results of the student who were taught by employing RME approach and problem posing approach, (iii) there is  a difference of mathematics learning results of the students who have very high and high motivation, (iv) there is interaction influence of learning approach with motivation on mathematics learning result, (v) there is no difference of mathematics learning results of the students who have very high and high motivation taught by employing RME approach, (vi) there is a difference af mathematics learning results of the student who have very high and high motivation taught by employing problem posing approach, (vii) there is no difference of mathematics learning results of the student who have very high motivation and taught by using RME approach and problem posing approach, and (viii) there is no difference of mathematics learning results  of the students who have high motivation and taught by using RME approach and problem posing approach